Kamchatka subduction zone, May 2013: the Mw 8.3 deep earthquake, preceding shallow swarm and numerous deep aftershocks - Špičák, A. (Aleš); Vaněk, J. (Jiří) (Studia Geophysica et Geodaetica, 2014)
A sequence of 98 teleseismically recorded earthquakes occurred off the east coast of Kamchatka at depths between 10-90 km around latitude 52.5°N and longitude 160°E on May 16-23, 2013. The swarm occurred along the northern limit of the rupture area of the 1952 Mw 9.0 great Kamchatka earthquake, the fifth largest earthquake in the history of seismic observations. On May 24, 2013 the strongest deep earthquake ever recorded of Mw 8.3 occurred beneath the Sea of Okhotsk at a depth of 610 km in the Pacific slab of the Kamchatka subduction zone, becoming the northernmost deep earthquake in the region. The deep Mw 8.3 earthquake occurred down-dip of the shallow swarm in a transition zone between the southern deep and northern shallow segments of the Pacific slab. Several deep aftershocks followed, covering a large, laterally elongated part of the slab. We suppose that the two described earthquake sequences, the May 16-23 shallow earthquake swarm and the May 24-28 deep mainshock-aftershock series, represent a single tectonic event in the Pacific slab having distinct properties at different depth levels.